Effect of Mineral or OFMSW Digestate Fertilization on Ryegrass and Nitrogen Leaching - Gabriella Rossi; Claudio Beni; Anna Benedetti; Barbara Felici; Ulderico Neri (Agronomy, 2023)
The current guidelines of waste management are aimed at the recovery and recycling of biowaste while respecting the protection of human health and the environment. The recent European legislation on fertilizers provides for the use of digestates derived from the organic fraction of municipal solid waste (OFMSW). The objectives of this study were to verify the fertilizing effect of three types of OFMSW digestates on the ryegrass culture comparing mineral fertilization and to evaluate the nitrogen lost to leaching in soil diversely fertilized following simulated rainfall. The ryegrass was grown in pots. The soil was fertilized with mineral fertilizer or OFMSW digestates. For each treatment, five mowing procedures were performed on the crop, and the ryegrass biomass production and nitrogen concentration were determined from the ryegrass samples. During the experiment, six rains were simulated, and the leached nitrogen was analyzed. The results showed that: (i) the fertilizing effect of OFMSW digestates on nitrogen nutrition of ryegrass was similar to ammonium sulphate fertilization, confirming the agronomic validity of these by-products to reduce the use of synthetic fertilizers; (ii) soil fertilization with OFMSW digestates had a positive effect limiting nitrogen loss due to leaching compared to mineral fertilization, highlighting the soil-improving properties of these by-products, in particular of the composted digestate.